Factors Influencing Trainee Enrolment in Modular Courses in Technical Training Institutes in Kenya - Karuru , Lucy Karuntimi; Nyaga , Julius (African Journal of Education,Science and Technology (AJEST), 2014)
Previously Technical Vocational Educational Training Institutions were offering Business Technical Education Programs as well as Technical Education Programs that would run for three years. However, in the year 2009, Modular courses were introduced and with them set in a decline in enrolment. Education is acknowledged as a means for transforming and empowering the youth with skills, knowledge and attitudes to enable them become productive members of the society. This underscores the importance played by education and training in the Kenyan development agenda. It is within this recognition that the social pillar of Kenya vision 2030 sets to invest in the people of Kenya in order to improve the quality of life for all Kenyans by targeting education and training among other programs. Most Technical Training Institutes have commendable physical infrastructure and adequate qualified personnel to achieve excellent training and high performance in external examinations. They also have rich catchments areas to supply them with trainees. However it has been observed that trainee enrolment in modular courses is below the stakeholders‟ expectations. Hence, this paper sets out to establish possible factors influencing trainee enrolment in modular courses in Technical Training Institutes. The paper set out to ascertain enrolment trends in Technical Training Institutes; to establish internal factors influencing enrolment in modular courses; to ascertain external factors influencing enrolment in modular courses; to establish challenges faced by trainees when transiting from one module to the next. The paper found out that the enrolment in non-modular courses was higher over the period under study than that in modular courses. It was also found out that the external factors were influencing enrolment to modular courses more than internal factors notably the examination policies, logistics and the curriculum. The paper recommends that technical training institutes be empowered to examine and issue certificates; Strengthen links between industry and training; Kenya Institute of Curriculum Development should review course duration; Institutes should intensify marketing of their courses.